Grupos de Implicação e Pesquisa e Organidrama como dispositivos de pesquisa e intervenção no mundo do trabalho - Matheus Viana Braz; Francisco Hashimoto (Universidade do Porto, 2020)
Clinical Sociology is characterized by the commitment of researchers to the construction of actions contrary to the logic of culpability and the individualization of the existential contradictions in the world of work. In this context, the purpose of this study is to understand the methodological and technical supports of two research and intervention devices in Clinical Sociology (the Implication and Research Groups and the Organidrame), in order to explore them as instruments for analyzing the conflicts experienced at work in our society. Through a qualitative, transversal, and descriptive approach, this study is part of the in-service research modality, starting from the production of knowledge from the professional activities developed by the researchers. The paper concludes with an explanation of the differentials of the devices, linked to the possibilities of working collectively on family, social and existential phenomena, but also political, ideological, and managerial ones engendered in the subjects' work contexts.